Intelligent dispatch for distributed renewable resources - Hopkins, Mark (Kansas State University, 2009)
A time may soon come where prices of electricity vary by time of day or season. Time of Day (TOD) pricing is considered by many to be a key part of creating a more energy-efficient and renewable-energy friendly grid. TOD pricing is also an integral part of Smart Grid and is already available to some customers. With TOD pricing becoming a reality, intelligent dispatching systems that utilize Energy Storage Devices (ESDs) to maximize the use of renewable resources, such as energy produced by small, customer owned wind generators and roof-top solar generators, and grid energy while determining the most economical dispatch schedule could play an important role for both the customer and the utility. This purpose of this work is to create an algorithm upon which these dispatching systems can be based. The details of one proposed algorithm are presented. The full development of the algorithm from its most simplistic form into a much more complex system that takes into account all of the major nonidealities of a real system is given. Additionally, several case studies are presented to show the effectiveness of the algorithm from both a technical standpoint and an economic standpoint. The case studies simulated both wind and solar powered devices using data taken in the state of Kansas, but case studies to emulate electric rates and renewable resources in other areas of the country are presented as well. For each of these case studies, 20 year net present value calculations are presented to determine the economic viability of both the renewable energy production and the dispatching systems.
Keywords: Dispatch; Renewable energy; Distributed generation; Energy storage device; Time of day pricing; Energy (0791); Engineering, Electronics and Electrical (0544)